Functionalized lignin-polylactic acid wood-plastic composite material and preparation method thereof
By functionalizing lignin with quaternary ammonium salt and blending it with polylactic acid, functionalized lignin-polylactic acid wood-plastic composite material was prepared, which solved the shortcomings of polylactic acid in antibacterial properties and achieved effective inhibition of bacteria. Improved mechanical properties of bacteria and materials.
Patent Information
- Application Number
- CN202411795600.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polylactic acid materials have shortcomings in antibacterial properties, making it difficult to effectively inhibit bacterial growth.
By functionalizing lignin with quaternary ammonium salts, functionalized lignin is formed, and blended with polylactic acid, a functionalized lignin-polylactic acid wood-plastic composite material is prepared. This material introduces antibacterial active groups through Mannich reaction and cross-linking reaction, improving antibacterial properties.
This material significantly improves the antibacterial effect on Streptococcus aureus and improves the mechanical strength and toughness of polylactic acid through chemical grafting.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, in particular to a functionalized lignin-polylactic acid wood-plastic composite material and a preparation method thereof. Background Art
[0002] Polylactic acid has good biocompatibility and biodegradability. It is a green and environmentally friendly material and is widely used in biomedicine, packaging and other fields. In recent years, the modification of polylactic acid has been a hot research topic. Blending polylactic acid with inorganic nanomaterials, high molecular polymers, etc. is an effective way to improve the comprehensive properties of polylactic acid, which can give polylactic acid excellent mechanical strength, antibacterial properties, flame retardancy, etc.
[0003] Polylactic acid can be compounded with natural polymers such as cellulose and starch to produce wood-plastic composite materials with excellent performance. Patent CN108003582B "A polylactic acid wood-plastic composite wire and its preparation method and application" discloses that the wire obtained by compounding polylactic acid with wood powder has good fluidity, flame retardancy and physical and mechanical properties. Lignin is widely present in wood and bark and is the main by-product of the cellulose industry. The recovery and development and utilization of lignin is imminent. Therefore, functional groups such as quaternary ammonium salts can be introduced into lignin, and then compounded with polylactic acid for modification. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a functionalized lignin-polylactic acid wood-plastic composite material and a preparation method thereof, which endows polylactic acid with excellent antibacterial properties.
[0005] To achieve the above object, the present invention provides the following technical solution: a functionalized lignin-polylactic acid wood-plastic composite material, and the preparation method of the functionalized lignin-polylactic acid wood-plastic composite material is as follows: (1) Add deionized water and sodium hydroxide to a reaction vessel, then add alkaline lignin, stir evenly, add glutaraldehyde, heat to 50-85 °C, react for 6-12 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0006] (2) Add N,N-dimethylformamide solvent, hydroxyethyl modified lignin and dodecyldimethyl-2-hydroxyammonium chloride into a reaction container, stir the solvent and then add toluene diisocyanate trimer and a catalyst, heat to react, add deionized water to precipitate after the reaction, filter the solvent, wash with deionized water and dichloromethane, and obtain quaternary ammonium salt functionalized lignin.
[0007] (3) Adding dichloromethane, polylactic acid and quaternary ammonium salt functionalized lignin into a reaction container, stirring evenly and then vacuum drying to remove the solvent, placing the materials in a twin-screw extruder, melting and extruding granulation, and injecting the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material.
[0008] Preferably, in step (1), the mass ratio of deionized water to sodium hydroxide is 100:0.2-0.35.
[0009] Preferably, in step (1), the mass ratio of alkali lignin to glutaraldehyde is 100:3-8.
[0010] Preferably, in step (2), the mass ratio of hydroxyethyl modified lignin, dodecyldimethyl-2-hydroxyammonium chloride, toluene diisocyanate trimer and catalyst is 100:12-35:7-20:0.05-0.15.
[0011] Preferably, the catalyst in step (2) is one of dibutyltin dilaurate and stannous octoate.
[0012] Preferably, the reaction temperature in step (2) is 70-110°C, and the reaction time is 10-30 h.
[0013] Preferably, in step (3), the mass ratio of polylactic acid to quaternary ammonium salt functionalized lignin is 100:25-40.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The functionalized lignin-polylactic acid wood-plastic composite material uses glutaraldehyde to react with the α-carbon atom at the position of the phenolic hydroxyl group of lignin to reduce the aldehyde group to generate a hydroxyl group, thereby obtaining hydroxyethyl-modified lignin, and then introducing the obtained active hydroxyethyl group into the lignin. Then, under the action of an organic tin catalyst, toluene diisocyanate trimer is used as a cross-linking agent, and the isocyanate group reacts with the hydroxyethyl group of the lignin and the hydroxyl group of dodecyl dimethyl-2-hydroxyammonium chloride respectively, thereby chemically grafting a long-chain alkyl quaternary ammonium salt into the lignin, and obtaining an antibacterial quaternary ammonium salt functionalized lignin.
[0015] Quaternary ammonium salt functionalized lignin is used as a functional filler and blended with polylactic acid to obtain a wood-plastic composite material. The quaternary ammonium salt grafted with lignin has excellent antibacterial and antibacterial spectrum, and has a good antibacterial effect on Staphylococcus aureus. The long-chain alkyl grafted with lignin is entangled with the polylactic acid molecular chain to form a good molecular chain force. The quaternary ammonium salt functionalized lignin is used as a physical cross-linking site, which has a good toughening effect on polylactic acid and can improve the toughness and mechanical strength of polylactic acid. DETAILED DESCRIPTION
[0016] To achieve the above purpose, the present invention provides the following embodiments and examples: A functionalized lignin-polylactic acid wood-plastic composite material, the preparation method of which is as follows: (1) Add deionized water and sodium hydroxide in a mass ratio of 100:0.2-0.35 to a reaction container, then add alkali lignin, stir evenly and add glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is 100:3-8, heat to 50-85°C, react for 6-12 hours, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0017] (2) Add N,N-dimethylformamide solvent, hydroxyethyl modified lignin and dodecyl dimethyl-2-hydroxyammonium chloride into a reaction container, stir the solvent and then add toluene diisocyanate trimer and a catalyst, wherein the mass ratio of hydroxyethyl modified lignin, dodecyl dimethyl-2-hydroxyammonium chloride, toluene diisocyanate trimer and catalyst is 100:12-35:7-20:0.05-0.15, and the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 70-110°C, react for 10-30 hours, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane, and obtain quaternary ammonium salt functionalized lignin.
[0018] (3) Adding dichloromethane, polylactic acid and quaternary ammonium salt functionalized lignin in a mass ratio of 100:25-40 into a reaction container, stirring evenly and then vacuum drying to remove the solvent, placing the material in a twin-screw extruder, melting and extruding granulation, and injecting the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material. Example 1
[0019] (1) Add 100 mL of deionized water and 0.2 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly, add 0.06 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 50 ° C, react for 6 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0020] (2) Add 50 mL of N,N-dimethylformamide solvent, 2 g of hydroxyethyl modified lignin and 0.24 g of dodecyl dimethyl-2-hydroxyammonium chloride into a reaction container, stir the solvent and then add 0.14 g of toluene diisocyanate trimer and 0.001 g of catalyst, the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 70 °C, react for 10 h, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane to obtain quaternary ammonium salt functionalized lignin.
[0021] (3) Add 100 mL of dichloromethane, 10 g of polylactic acid and 2.5 g of quaternary ammonium salt functionalized lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material. Example 2
[0022] (1) Add 100 mL of deionized water and 0.25 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly, add 0.08 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 65 ° C, react for 10 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0023] (2) Add 100 mL of N,N-dimethylformamide solvent, 2 g of hydroxyethyl modified lignin and 0.4 g of dodecyl dimethyl-2-hydroxyammonium chloride into a reaction vessel, stir the solvent and then add 0.2 g of toluene diisocyanate trimer and 0.001 g of catalyst, the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 110 °C, react for 10 h, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane to obtain quaternary ammonium salt functionalized lignin.
[0024] (3) Add 200 mL of dichloromethane, 10 g of polylactic acid and 2.8 g of quaternary ammonium salt functionalized lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material. Example 3
[0025] (1) Add 100 mL of deionized water and 0.28 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly and add 0.12 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 75 ° C, react for 8 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0026] (2) Add 150 mL of N,N-dimethylformamide solvent, 2 g of hydroxyethyl modified lignin and 0.5 g of dodecyl dimethyl-2-hydroxyammonium chloride into a reaction container, stir the solvent and then add 0.25 g of toluene diisocyanate trimer and 0.002 g of catalyst, the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 100 °C, react for 24 h, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane to obtain quaternary ammonium salt functionalized lignin.
[0027] (3) Add 300 mL of dichloromethane, 10 g of polylactic acid and 3.2 g of quaternary ammonium salt functionalized lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material. Example 4
[0028] (1) Add 100 mL of deionized water and 0.3 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly, add 0.14 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 70 ° C, react for 12 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0029] (2) Add 200 mL of N,N-dimethylformamide solvent, 2 g of hydroxyethyl modified lignin and 0.6 g of dodecyl dimethyl-2-hydroxyammonium chloride into a reaction vessel, stir the solvent and then add 0.32 g of toluene diisocyanate trimer and 0.002 g of catalyst, the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 100 °C, react for 18 h, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane to obtain quaternary ammonium salt functionalized lignin.
[0030] (3) Add 500 mL of dichloromethane, 10 g of polylactic acid and 3.5 g of quaternary ammonium salt functionalized lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material. Example 5
[0031] (1) Add 100 mL of deionized water and 0.35 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly and add 0.16 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 85 ° C, react for 12 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0032] (2) Add 200 mL of N,N-dimethylformamide solvent, 2 g of hydroxyethyl modified lignin and 0.7 g of dodecyl dimethyl-2-hydroxyammonium chloride into a reaction container, stir the solvent and then add 0.4 g of toluene diisocyanate trimer and 0.003 g of catalyst, the catalyst is one of dibutyltin dilaurate or stannous octoate, heat to 110 °C, react for 30 h, add deionized water after the reaction for precipitation, filter the solvent, wash with deionized water and dichloromethane to obtain quaternary ammonium salt functionalized lignin.
[0033] (3) Add 500 mL of dichloromethane, 10 g of polylactic acid and 4 g of quaternary ammonium salt functionalized lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material.
[0034] Comparative Example 1 (1) Add 100 mL of deionized water and 0.3 g of sodium hydroxide in a mass ratio into a reaction container, then add 2 g of alkali lignin, stir evenly and add 0.12 g of glutaraldehyde, the mass ratio of alkali lignin to glutaraldehyde is, heat to 70 ° C, react for 12 h, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin.
[0035] (2) Add 400 mL of dichloromethane, 10 g of polylactic acid and 3 g of hydroxyethyl modified lignin into a reaction container, stir evenly and then vacuum dry to remove the solvent. Place the material in a twin-screw extruder, melt and extrude into granules, and inject the masterbatch into granules to obtain a lignin-polylactic acid wood-plastic composite material.
[0036] Antibacterial performance test: The functionalized lignin-PLA wood-plastic composite material and the lignin-PLA wood-plastic composite material in the embodiment and the comparative example were pressed into a film material with a thickness of 2 mm, placed at the bottom of a sterile culture dish, and then dripped with a concentration of 5×10 6 CFU / mL of the Staphylococcus aureus suspension was added with beef extract peptone medium and cultured in a constant temperature incubator for 6 h, and the concentration of the suspension after culture was determined.
[0037]
Claims
1. A functionalized lignin-polylactic acid wood-plastic composite material, characterized in that: The preparation method of the functionalized lignin-polylactic acid wood-plastic composite material is as follows: (1) Add deionized water and sodium hydroxide to a reaction container, then add alkali lignin, stir evenly, add glutaraldehyde, heat to 50-85°C, react for 6-12 hours, add deionized water to dilute after the reaction, filter the solvent, wash with deionized water and ethanol until neutral, and obtain hydroxyethyl modified lignin; (2) adding N,N-dimethylformamide solvent, hydroxyethyl modified lignin and dodecyl dimethyl-2-hydroxyammonium chloride into a reaction container, stirring the solvent and then adding toluene diisocyanate trimer and a catalyst, heating to react, adding deionized water to precipitate after the reaction, filtering the solvent, washing with deionized water and dichloromethane, and obtaining quaternary ammonium salt functionalized lignin; (3) Adding dichloromethane, polylactic acid and quaternary ammonium salt functionalized lignin into a reaction container, stirring evenly and then vacuum drying to remove the solvent, placing the materials in a twin-screw extruder, melting and extruding granulation, and injecting the masterbatch into a mold to obtain a functionalized lignin-polylactic acid wood-plastic composite material.
2. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: In the step (1), the mass ratio of deionized water to sodium hydroxide is 100:0.2-0.
35.
3. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: In the step (1), the mass ratio of alkali lignin to glutaraldehyde is 100:3-8.
4. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: In the step (2), the mass ratio of hydroxyethyl modified lignin, dodecyl dimethyl-2-hydroxyammonium chloride, toluene diisocyanate trimer and catalyst is 100:12-35:7-20:0.05-0.
15.
5. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: The catalyst in step (2) is one of dibutyltin dilaurate and stannous octoate.
6. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: The reaction temperature in step (2) is 70-110°C and the reaction time is 10-30 h.
7. The functionalized lignin-polylactic acid wood-plastic composite material according to claim 1, characterized in that: In the step (3), the mass ratio of polylactic acid to quaternary ammonium salt functionalized lignin is 100:25-40.
Citation Information
Patent Citations
A polylactic acid wood-plastic composite wire, its preparation method and application
CN108003582B
Cited By
Weather-resistant biomass sheet regulation and control process based on multi-scale collaboration
CN122539695A